Clinical Features, Treatment Courses, and Distribution of Cytomegalovirus Genotypes among Thrombocytopenia Patients Aged Younger than 12 Months - Hu, Hongbo; Cheng, Ying; Peng, Qiaoying; Chen, Kun (American Journal of Perinatology, 2020)
Objective The aims of this study were to evaluate the clinical characteristics, laboratory data, and treatment of the cytomegalovirus (CMV)-associated thrombocytopenia in infants aged younger than 12 months and to investigate the possible relationship between genotypes of glycoprotein B (gB) and glycoprotein H (gH) and CMV-associated thrombocytopenia.Study Design Infants with positive identification of cytomegalovirus (CMV) and thrombocytopenia, being treated at Hubei Maternal and Child Health Hospital from January 2015 to June 2019 were included. Genotype of gB and gH analysis were done by nested polymerase chain reaction (nPCR) and restrictions length polymorphism.Results The prevalence of CMV congenital, perinatal, and postnatal infection were 1.4% (76/5428), 29.1% (378/1301), and 41.8% (243/581), respectively. A total of 29 immunocompetent patients with CMV-associated thrombocytopenia were analyzed, including 7 (9.2%, 7/76) congenital infections, 14 (3.7%, 14/378) perinatal infections, and 8 (3.3%, 8/243) postnatal infections. Platelet count at diagnosis <20 × 109/L was the common hematologic finding of CMV-associated thrombocytopenia in perinatal infection (1/7 congenital infection vs. 10/14 perinatal infection vs. 3/8 postnatal infection, Chi-square (χ2) = 6.616, p = 0.037). Notably, significantly higher frequency of hepatobiliary symptoms was found in congenital and perinatal infections groups (4/7 congenital infection vs. 10/14 perinatal infection vs. 1/8 postnatal infection, χ2 = 7.188, p = 0.027). Intravenous immunoglobulin was prescribed for 24 (82.8%, 24/29) patients, and antiviral agents were prescribed for 9 (31.0%, 9/29) patients. The most prevalent genotypes of CMV in the study were gB1 (60.7%, 17/28) and gH2 (57.1%, 16/28).Conclusion There was a substantial percentage of symptomatic CMV infection in patients aged younger than 12 months. Thrombocytopenia is one of the common clinical manifestations in congenital CMV infection. The gB1 genotype had more virulence in infants with acquired CMV infection. There might be an association between gH2 genotype of CMV and CMV-associated thrombocytopenia.
Keywords: cytomegalovirus; cytomegalovirus-associated thrombocytopenia; glycoprotein B; glycoprotein H